2018
DOI: 10.1101/278697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-Random Mis-Segregation of Human Chromosomes

Abstract: Summary: Recurrent patterns of chromosomal changes (aneuploidy) are widespread in cancer. These patterns are mainly attributed to selection processes due to an assumption that human chromosomes carry equal chance of being mis-segregated into daughter cells when fidelity of cell division is compromised. Human chromosomes vary widely in size, gene density and other parameters that might generate bias in mis-segregation rates, however technological limitations have precluded a systematic and high throughput analy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(56 citation statements)
references
References 74 publications
(74 reference statements)
3
47
6
Order By: Relevance
“…The findings by Drpic et al and Worrall and coworkers are fully in tune with our NCH149 data, which show a significantly increased rate of large chromosomes sequestered into micronuclei in human cancer cells. Mechanistically, both cohesion fatigue and chromosome lagging related to kinetochore size might contribute.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The findings by Drpic et al and Worrall and coworkers are fully in tune with our NCH149 data, which show a significantly increased rate of large chromosomes sequestered into micronuclei in human cancer cells. Mechanistically, both cohesion fatigue and chromosome lagging related to kinetochore size might contribute.…”
Section: Resultssupporting
confidence: 90%
“…This effect was further increased when erroneous attachments were enhanced by monastrol treatment . Similarly, it has most recently been shown that the largest chromosomes 1 and 2 are particularly prone to missegregation in human retinal pigment epithelium cells (RPE1) following mitotic spindle disruption by release from a nocodazole‐mediated mitotic arrest . In this study, chromosomes 1 and 2 together made up for more than one‐third of anaphase lagging chromosomes as a consequence of cohesion fatigue, a gradual failure of the cohesive forces holding sister chromatids together, leading to premature sister chromatid separation.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Interestingly, in the RPE-1 cell line, chromosome 1, that carries a large centromere, tends to lag (likely due to merotelic attachment) at a higher frequency than chromosomes with a smaller centromere, such as chromosome 3, even in unperturbed conditions (Fig 2E and data not shown). Accordingly, chromosome 1 was recently found to be lost at higher frequency compared to others following nocodazole release (Worrall et al, 2018), a treatment known to promote merotelic attachment (Crasta et al, 2012). This suggests that stronger centromeres, as the ones from chromosome 1, are less affected in conditions that compromise centromere function, but more vulnerable to incorrect attachment.…”
Section: Discussionmentioning
confidence: 99%